Four essays on climate, energy, and sports economics - Kempa, Karol; Justus Liebig University Giessen (My University, 2018)
This dissertation consists of two main parts with different themes that are analysed in two papers, respectively. The first part consists of theoretical analyses of topics in the area of energy and climate economics. Climate change caused by greenhouse gas emissions is one of the greatest (economic) challenges of our time. Limiting global warming requires an understanding of the interaction between economic activity, energy use, emissions, and energy-saving/clean technologies. In particular, knowing the underlying market failures that prevent the first-best outcome is a prerequisite for designing and implementing effective and efficient policy instruments The paper Climate Policy with the Chequebook An Economic Analysis of Climate Investment Support (Chapter 2), co-authored with Ulf Moslener, identifies and characterises main market failures related to climate mitigation investments, in particular clean energy, and discusses recent trends in international climate policy, which seems to have shifted from debating emission targets towards financing commitments. The paper provides policy recommendations on the choice of finance instruments to address the identified market failures as well as guidance on how to use these instruments in order to reduce the risk of inefficient public spending. The second paper Directed Technical Change and Energy Intensity Dynamics: Structural Change vs. Energy Efficiency (Chapter 3), co-authored with Christian Haas, investigates two core drivers of energy intensity reductions: the adoption of more efficient production technologies (efficiency effect) and the adjustments of the structural composition of economic activity (structural effect). Using a theoretical model with directed technical change, this paper provides new insights on the effects of energy price growth and endogenous technical change on energy intensity developments. The simulation results for 26 OECD countries are largely consistent with the empirical evidence.The second part of this doctoral thesis addresses labour market issues that are empirically analysed based on professional sports data. Professional sports provide a unique laboratory for labour market research. One advantage is the detailed and accurate information on attributes, performance, and earnings of individuals. Furthermore, individuals´ actions within sports contests are observable and well documented, which offers a unique setting to study behaviour. The paper Misconduct and Leader Behaviour in Contests New Evidence from European Football (Chapter 4), co-authored with Hannes Rusch, provides an empirical investigation of severe misconducts in contests using data from European football. The paper differentiates between two types of misconduct both resulting in a yellow card, namely dissents against the authority in charge of enforcing the contest´s rules, i.e. the referee, and other misconducts aimed at the opposing team directly, i.e. fouls (sabotage). The findings indicate that teams with lower ability are more likely to commit sabotage. Dissent with the referee is affected by the current score of the match: the more unfavourable the score, the more likely is dissent with the referee. As (severe) punishment seems to deter misconducts, it could be a possible measure to prevent or at least reduce illegal behaviour in contests. Finally, the paper Generalists vs. Specialists: Skill Variety and Remuneration in Football (Chapter 5) investigates the remuneration of generalists versus specialists. Using data from the German football Bundesliga, I measure whether a player is rather a specialist in one task or a generalist, able to perform several tasks. Results indicate that defenders and forwards receive returns to skill specialisation, while midfielders do not. An explanation might be that midfielders are similarly engaged in offensive and defensive plays, while defenders and forwards mainly perform either defensive or offensive tasks. Thus, returns to specialisation disappear for occupations involving a wide range of tasks, indicating a trade-off between skill specialisation and versatility.
Keywords: ddc:330